Differential Sensitivity to In Vitro Inhibition of Cytochrome P450 Aromatase (CYP19) Activity Among 18 Freshwater Fishes. (17th May 2019) - Doering, Jon A; Villeneuve, Daniel L; Fay, Kellie A; Randolph, Eric C; Jensen, Kathleen M; Kahl, Michael D; LaLone, Carlie A; Ankley, Gerald T
Abstract: There is significant concern regarding potential impairment of fish reproduction associated with endocrine disrupting chemicals. Aromatase (CYP19) is a steroidogenic enzyme involved in the conversion of androgens to estrogens. Inhibition of aromatase by chemicals can result in reduced concentrations of estrogens leading to adverse reproductive effects. These effects have been extensively investigated in a small number of laboratory model fishes, such as fathead minnow ( Pimephales promelas ), Japanese medaka ( Oryzias latipes ), and zebrafish ( Danio rerio ). But, differences in sensitivity among species are largely unknown. Therefore, this study took a first step toward understanding potential differences in sensitivity to aromatase inhibitors among fishes. Specifically, a standard in vitro aromatase inhibition assay using subcellular fractions of whole tissue homogenates was used to evaluate the potential sensitivity of 18 phylogenetically diverse species of freshwater fish to the nonsteroidal aromatase inhibitor fadrozole. Sensitivity to fadrozole ranged by more than 52-fold among these species. Five species were further investigated for sensitivity to up to 4 additional nonsteroidal aromatase inhibitors, letrozole, imazalil, prochloraz, and propiconazole. Potencies of each of these chemicals relative to fadrozole ranged by up to 2 orders of magnitude among the 5 species. Fathead minnow, Japanese medaka, and zebrafish were among the least sensitive to all the investigated chemicals; therefore, ecological risks of aromatase inhibitors derived from these species might not be adequately protective of more sensitive native fishes. This information could guide more objective ecological risk assessments of native fishes to chemicals that inhibit aromatase.